A comparison between office rent determinants of Istanbul and other major metropolitan areas - V.Atilla Oven; Dilek Pekdemir (European Regional Science Association (ERSA), 2004)
Office rent determinants are well established for various metropolitan areas in the US [2, 3, 25] and some other international centres in Europe, especially in the UK [12, 17, 28]. The site selection and investment decisions for new office construction will largely depend on the information how office rent determinants are ranked according to their importance. For this purpose, the ranking of 52 office rent determinants for the metropolitan area of Istanbul are presented using the technique of factor analysis, and later compared with the reported findings of available major metropolitan areas. It has been found that, the only parameter commonly found significant is the vacancy rate. The results point out that regional differences and different economic conditions can significantly alter the perceived importance of rental determinants. Keywords: office rent determinants, factor analysis.
Keywords: 330; office rent determinants; factor analysis